A living tower: Using architecture for sustainable future growth - Scott, Jacobus Olivier (School of Architecture, Planning and Geomatics, 2017)
This thesis demonstrates how architectural design can be used to help alleviate the current environmental crisis, using a radical sustainable approach that integrates high density living and farming activities within the context of suburban planning. In South Africa, population growth and urbanisation have led to low-rise low-density buildings invading . bio diversity nodes, valuable arable land, and natural reserves on the periphery of cities. Not only are the infrastructural costs of servicing these low-density suburbs very high, but the pollution caused by daily commuting to and from the workplace has lasting environmental consequences. Continuing deforestation is needed to create new arable land; at the same time, ploughing and shipping within the agricultural sector make a significant contribution to global pollution, while up to 70% of potable water is lost through evaporation during irrigation. The architectural approach on which this thesis is based, integrates the usually separate components of living and farming, into a single closed high-rise entity, called the Living Tower. Taking a cue from ecosystem dynamics, a Living Tower model was developed to mimics the natural process whereby the waste of one entity becomes the food of another, creating an efficient cyclical flow of resources. In this way, renewable resources comprise the heart of the life-giving and life-sustaining Tower. Analysis of earlier designs based on similar principles is used to identify key elements of the Living Tower. These include amongst other integrated stacked greenhouses, evaporative coolers, an anaerobic digester, a central atrium design and a living machine (eco restorer). Living Tower models of differing heights are compared and evaluated in terms of their sustainability and efficiency. A thirty storey Living Tower is shown to provide the optimal solution to the core environmental issues considered, including the renewal of natural resources and the reclaiming of arable land. The corresponding diagrams, calculations and graphs illustrate the potential impact on both nature and society of a thirty storey Living Tower. This innovative design solution focuses on shaping the landscape with contextual reference in order for the Tower to 'grow' out of the hills and include a variety of mixed used programs in the form of living, working and playing to enhance social interaction. Through the design solutions the Living Tower successfully combines higher living densities and an ecologically friendly lifestyle in a structure that is economically viable, aesthetically pleasing, and therefore using architecture for sustainable future growth.